The enhancement of hemodynamic performance in Fontan circulation using pain free spontaneous ventilation - Rahman, Ali; Üstündag, Bilal; Burma, Oktay; Özercan, Ibrahim Hanifi; Erol, Fatih Serhat (My University, 2001)
Objective: Positive pressure ventilation is known to have a deleterious effect on pulmonary blood flow in patients with Fontan physiology. We evaluated the hemodynamic effects of pain free, spontaneous, non-positive pressure ventilation in patients undergoing Fontan staging procedures or completion. Fontan procedures, with creation of low pressure passive pulmonary circulation. Methods: Between May 1997 and May 1999 50 consecutive patients undergoing either bi-directional Glenn (BDG, n=23) or completion Fontan (n=27), were managed with early extubation. Anaesthetic management included continuous narcotics, caudal block, epidural block, or hyperbaric spinal. Post-operative management included low dose dopamine (3 mcg/kg per min), nitro-glycerine (0.3 mcg/kg per min) and nitroprusside (0.3 mcg/kg per min). Post-operative management was identical for all patients. Twelve patients were randomly selected to undergo continuous cardiac output and cardiac index (CI) determinations utilizing extra vascular Doppler probes placed on the ascending aorta, allowing for continuous aortic diameter and Doppler wave form velocity recordings. All patients were extubated either in the operating room or within one hour post-operatively. There were no deaths and no complications in the series. Mean length of stay (LOS) for BDG was 4.3±0.5 days. Mean LOS for Fontan patients was 11±4 days. Results: Mean pulmonary artery pressure (MPAP) fell from 19±3.464 pre-extubation to 14±3.271 immediately post-extubation, 13.2±2.261 6 h post-extubation, and 11.7±2.146 12 h post-extubation. All decreases in MPAP post-extubation were significant (P=<0.05). CI pre-extubation was 3.25±1.09, immediately post-extubation 5.05±1.297, 12 h post-extubation 6.225±1.19. All increases in CI post-extubation were significant (P=<0.05). Conclusion: Resumption of pain free, spontaneous, non-positive pressure ventilation enhances hemodynamic performance in patients with Fontan circulation and clearly improves outcome. Copyright © 2001 Elsevier Science B.V.
Keywords: Bi-directional Glenn shunt; Fontan